Reconceptualizing Noticing: Exploring Metacognitive Awareness through Written Reflection in EFL Learning - Sutriyani, Sutriyani; Retnowati, Nanik; Furqan, Muhammad (UICELE, 2026)
Noticing is commonly understood as learners’ awareness of language forms during the learning process. However, in natural classroom settings, noticing may extend beyond linguistic forms to include learners’ awareness of their own learning processes. Reflection, in this context, can function as a metacognitive strategy that supports such awareness. This study aims to explore how learner noticing emerges in written reflections and how it reflects both language awareness and metacognitive engagement. This study employed a descriptive qualitative approach, using data from five written reflections produced by pre-service teachers in an English Language Education program after completing classroom learning activities. The analysis was guided by theory-based noticing categories and reflection frameworks to examine how learners express their awareness linguistically. The findings reveal that learners’ noticing is predominantly directed toward their learning processes rather than specific language forms. Students frequently reported difficulties, challenges in understanding input, changes in their comprehension, and personal factors influencing their readiness to learn. These patterns indicate that written reflection encourages learners to engage in metacognitive noticing by making their learning processes more visible and structured. This study suggests that reflective writing in English not only enhances learners’ awareness of how they learn but also supports their ability to articulate learning experiences in a coherent and meaningful way. Thus, reflection serves as a valuable pedagogical tool to activate metacognitive strategies while maintaining relevance to the concept of noticing in language learning.